An exploratory survey of the digital technology readiness of the health care workforce across nine EU member states - Wells, John SG; Scheibein, Florian; Palese , Alvisa; Barać, Ivana; Beger, Jan; Bikava, Ieva; Bredelytė, Aelita; Byrne, Keith; Cleary, Frances; Cooney-Miner, Dianne; Dalluege, Andreas; Dobrowolska, Beata; et al. (Nursing in the 21st Century, 2025)
Introduction. Recent crises such as COVID-19, cyber-attacks on health care digital infrastructure, mass migration and war, highlight the crucial role of digital technology in service delivery. The establishment of the EU4 Health Programme in 2021, emphasized the need for an EU wide comprehensive enhancement of workforce digital skills with an emphasis on crisis resilience. At present there is almost no comparative EU wide workforce survey research in this area to inform effective policy implementation.Aim. To explore the use of digital technologies, the expressed training needs, the wellbeing and perception of organisational capacities referenced to digital technology across health care workforce in nine European Union states.Methods. A 36-item survey was developed focused on digital competencies, digital use, cybersecurity awareness, training needs, sense of wellbeing and perception of organisational readiness to implement digital change, utilising convenience sampling. For purposes of analysis workforce respondents were divided between clinical and non-clinical staff. Data was analysed using SPSS according to a pre-registered analysis plan.Results. After data cleaning, 2,028 respondents’ answers were analysed. Non-clinical staff demonstrated higher proficiency and usage rates in digital technologies. Significant differences between non-clinical and clinical staff were noted in security awareness, with clinical staff having significantly less knowledge/ awareness. All respondents perceived their organisations as only moderately ready to implement digital health care change.Conclusions. These exploratory results highlight need for policy development and interventions that enhance digital competencies across the EU health workforce. The results also suggest there is a need to address organisational capacities to support both training of the workforce and effective use of the workforce’s digital skills once these are acquired.